Mastering OpenCV with practical computer vision projects. - Baggio, Daniel Lélis (Packt Pub., 2012)
This is the definitive advanced tutorial for OpenCV, designed for those with basic C++ skills. The computer vision projects are divided into easily assimilated chapters with an emphasis on practical involvement for an easier learning curve. Cool, fun and advanced projects that cover the various aspects of OpenCV programming Strong emphasis on programming techniques and methodology for the best approach to each project Ten projects that are carefully designed to build on your skills at every step In Detail OpenCV is a computer vision library that is extensively used in companies, research groups and governmental bodies for real-time capture, video file import, image manipulation, object detection and much more. Its comprehensive set of computer vision and machine learning algorithms makes it the obvious choice for professionals to develop visual applications. With this book in hand, you would not need to plow through several pages of theory as this book will take you through the creation of many exciting projects that showcase the huge range of possibilities that open up when OpenCV is exploited to its full potential.